178k views
0 votes
Ronald started solving the equation −2(2x−4)+3=6x+1.

Which is a correct next step?

User Brad Lanam
by
5.7k points

2 Answers

4 votes

Answer:

distribute bud

Explanation:

distribute throught the parethesis first

User Nikhilesh Patve
by
5.1k points
0 votes

Answer:

x = 1

Explanation:

-2(2x - 4) + 3 = 6x + 1

~Distribute left side

-4x + 8 + 3 = 6x + 1

~Simplify left side

-4x + 11 = 6x + 1

~Subtract 11 to both sides

-4x = 6x - 10

~Subtract 6x to both sides

-10x = -10

~Divide -10 to both sides

x = 1

Best of Luck!

User Kaja
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.